Multirepresentation Ability Analysis of Wave Matter Using Physics Education Technology - iryan dwi handayani; Puri Muliandhi; Wahjoerini (Jurnal Penelitian Pendidikan IPA, 2024)
Education is the primary capital of a nation's progress, because with education, the human resources that a nation possesses will become quality. Physics is a branch of natural science, specifically studying natural phenomena and events through several scientific and systematic methods. The research is aimed at developing a tool to evaluate the multirepresentation of wave matter using Physics Education Technology. The methods used in this research are quantitative methods and the research is carried out by providing filling issues that will analyze verbal multirepresentation capabilities, tables and graphs. The research will be carried out at Semarang University using samples of civil engineering students. Research procedures through preliminary stages by drawing up a research plan. Preparing and compiling wave learning modules using the simulation facilities of Physics Education Technology, then compiling evaluation tools that are subject-based with multi-representation verbal approaches, tables and graphs. Validation of learning modules and evaluation tools to determine whether it is worthy of use or not, validation is carried out by 2 experts. Validation of test instruments by experts on material aspects averaged 93%, on construction aspects 94% and on language aspects reached 92%, of which results show that the instruments have excellent validity. In the finite scale test, the highest multirepresentation ability is communicating from mathematics to verbal and its mathematical abilities, while the lowest is in the ability to picture to mathematics and physics.